Workshop Report on Gender Equality and Social Inclusion (GESI) in Agribusiness Ecosystems in Zambia - International Institute of Tropical Agriculture (CGIAR System Organization, 2022)
It cannot be overemphasized that creating equal opportunities for women, men and youths can foster socio-economic development through agri-business in various agricultural value chains in Zambia. Women can potentially be drivers of agricultural transformation in Africa, especially in Zambia, because they hold the key to improving their families’ livelihoods and food security. However, constraints such as lack of access to initial capital, machinery, reliable markets, control and ownership of productive assets, and relevant training are challenging to overcome, leading to restricted participation by women and youths in agricultural systems. For this reason, a workshop was held to conceptualize Gender Equality and Social Inclusion (GESI) in Agribusiness Ecosystems; identify and collect data on successful agribusiness projects in Zambia; address gender-based constraints for women, youth and persons with disabilities active participation in agribusiness ecosystem in Zambia; and establish a pan ESA GESI agribusiness network. To achieve the set objectives, stakeholders comprising government agencies, NGOs, traditional leaders, female and youth farmer groups and individual farmers were brought together to discuss and share experiences on various aspects of GESI in Agribusiness for sustainable livelihoods.